2019
DOI: 10.3389/fmicb.2019.01025
|View full text |Cite
|
Sign up to set email alerts
|

Non-sterile Submerged Fermentation of Fibrinolytic Enzyme by Marine Bacillus subtilis Harboring Antibacterial Activity With Starvation Strategy

Abstract: Microbial fibrinolytic enzyme is a promising candidate for thrombolytic therapy. Non-sterile production of fibrinolytic enzyme by marine Bacillus subtilis D21-8 under submerged fermentation was realized at a mild temperature of 34°C, using a unique combination of starvation strategy and self-production of antibacterial agents. A medium composed of 18.5 g/L glucose, 6.3 g/L yeast extract, 7.9 g/L tryptone, and 5 g/L NaCl was achieved by conventional and statistical methods. Results showed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 43 publications
1
12
0
Order By: Relevance
“…Marine microorganisms producing fibrinolytic enzymes, including bacteria (Streptomyces lusitanus [43], Streptomyces radiopugnans VITSD8 [44], Streptomyces violaceus VI-TYGM [45], Pseudomonas aeruginosa KU1 [46,47], Alteromonas piscicida [48], Pseudoalteromonas sp. IND11 [49], bacterial strain GPJ3 [50], Marinobacter aquaeolei MS2-1 [51], Bacillus flexus [52], Bacillus subtilis [53], Bacillus subtilis HQS-3 [54], Bacillus vallismortis [55], Bacillus subtilis D21-8 [56], Bacillus pumilus BS15 [29], Bacillus subtilis WR350 [57], Bacillus subtilis JS2 [58], Bacillus velezensis BS2 [59], Bacillus subtilis ICTF-1 [41], Shewanella sp. IND20 [60], Serratia rubidaea KUAS001 [61] and Serratia marcescens subsp.…”
Section: Marine Microorganisms As Sources Of Fibrinolytic Enzymementioning
confidence: 99%
See 1 more Smart Citation
“…Marine microorganisms producing fibrinolytic enzymes, including bacteria (Streptomyces lusitanus [43], Streptomyces radiopugnans VITSD8 [44], Streptomyces violaceus VI-TYGM [45], Pseudomonas aeruginosa KU1 [46,47], Alteromonas piscicida [48], Pseudoalteromonas sp. IND11 [49], bacterial strain GPJ3 [50], Marinobacter aquaeolei MS2-1 [51], Bacillus flexus [52], Bacillus subtilis [53], Bacillus subtilis HQS-3 [54], Bacillus vallismortis [55], Bacillus subtilis D21-8 [56], Bacillus pumilus BS15 [29], Bacillus subtilis WR350 [57], Bacillus subtilis JS2 [58], Bacillus velezensis BS2 [59], Bacillus subtilis ICTF-1 [41], Shewanella sp. IND20 [60], Serratia rubidaea KUAS001 [61] and Serratia marcescens subsp.…”
Section: Marine Microorganisms As Sources Of Fibrinolytic Enzymementioning
confidence: 99%
“…Similarly, Anusree and colleagues (2020), by using submerged fermentation, were able to improve the expression of fibrinolytic enzyme from a bacterium Serratia rubidaea KUAS001 obtained from marine milieus [61]. In addition, Pan and colleagues (2019) showed the utilization of non-sterile submerged fermentation to minimize the production cost of enzymes from Bacillus subtilis D21-8 [56]. Moreover, several researchers showed that the use and application of diverse statistical tools, such as Box-Behnken design [46], two-level full factorial design (2 5 ) [49,52,60], response surface methodology [52,60,72,81], Plackett-Burman design [64,81], one-factor experiment [64], L 18 -orthogonal array method [41] and central composite experimental design [49,67], are useful approaches for optimizing physico-chemical parameters for the production of fibrinolytic enzymes.…”
Section: Fermentation Approachmentioning
confidence: 99%
“…Strains that offer the possibility to operate under non-sterile conditions have become one of the most commercially appealing options when it comes to industrial production [ 42 , 43 ]. It is already known that Pt is barely available in the environment and therefore can hardly be used by other organisms [ 24 ].…”
Section: Resultsmentioning
confidence: 99%
“…Anusree et al optimized the production of fibrinolytic enzyme isolated from Serratia rubidaea KUAS001 by using submerged fermentation (Anusree et al, 2020). Staphylokinase (SAK) from Staphylococcus aureus GH38 was also screened by using submerged fermentation (Noori and Aziz, 2020); while Pan et al reported for the first time the use of non-sterile submerged-fermentation to reduce the production cost of fibrinolytic enzyme from Bacillus subtilis D21-8 (Pan et al, 2019a). Furthermore, use of different statistical tools such as Box-Benhken design (Kumar et al, 2018), two-level full factorial design (2 5 ) (Vijayaraghavan et al, 2016a;Vijayaraghavan et al, 2016b), response surface methodology (RSM), central composite design (CCD) and artificial neural network (ANN) (Chandramohan, et al, 2019;Joji et al, 2019), as well as orthogonal experiment (Wu et al, 2019) have been reported to optimize the concentration of media components used for fermentation to obtain fibrinolytic enzymes in order to enhance their production yield.…”
Section: Microorganisms As Sources Of Fibrinolytic Enzymesmentioning
confidence: 99%